XIV Congress of Russian Children’s Infectiologists «Current Issues of Infectious Diseases and Vaccination» came off in Moscow - Article Editorial (Детские инфекции (Москва))
11—12 December 2015 XIV Congress of Russian Children’s Infectiologists «Current Issues of Infectious Diseases and Vaccination» came off in Moscow.